-(-16-8x)=(6x-4)

Simple and best practice solution for -(-16-8x)=(6x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-16-8x)=(6x-4) equation:



-(-16-8x)=(6x-4)
We move all terms to the left:
-(-16-8x)-((6x-4))=0
We add all the numbers together, and all the variables
-(-8x-16)-((6x-4))=0
We get rid of parentheses
8x-((6x-4))+16=0
We calculate terms in parentheses: -((6x-4)), so:
(6x-4)
We get rid of parentheses
6x-4
Back to the equation:
-(6x-4)
We get rid of parentheses
8x-6x+4+16=0
We add all the numbers together, and all the variables
2x+20=0
We move all terms containing x to the left, all other terms to the right
2x=-20
x=-20/2
x=-10

See similar equations:

| 40+0.30x=20+0.40x | | -12x+3=2x+31 | | 14x+8=41 | | 15p-9=7p+1 | | -(-16-8x)=(6x-4 | | b/11-7b=24/11 | | 4x+2(4x-8)-4=-56 | | X+1/8x=126 | | y/10-70=-67 | | 2×5x=4x | | 10.9+3x-5=13 | | -214=5(7x+2)-3x | | (d)=25+20d | | 2x-3x+4=1 | | (4y+32)-7=15 | | -u+18=201 | | 10=v-1 | | -13.13-13.2z=-3.1z | | p/3+4=5 | | -5(x-3)=-4(x-6) | | 4.97+1.97+(x/2)=12.92 | | -3(11r+5)=3(-9r+9) | | 2p+p+(2)(9)=3p+18 | | 29-15x=-x-3 | | -19+15b-17=-15+12b | | y=(93)93+40 | | 8+2y-8=3(y-11) | | 2=g/6-2 | | -x+7=−x+7=-4x-20 | | -4(1-p)=6(p-2) | | 5x+7x=9x-3 | | |2x+4|=30 |

Equations solver categories